Penguatan Karakter Religius Pemuda Melalui Internalisasi Nilai Pendidikan Islam Berbasis Kearifan Lokal di Kecamatan Lumbang, Kabupaten Probolinggo - Bulhayat Bulhayat; Aziz Akbar (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Islamic education faces challenges in internalizing religious values, especially among youth who are susceptible to the influence of globalization and foreign cultures. Conventional approaches are less effective in reaching the younger generation who are familiar with the digital age. Therefore, a more relevant and adaptive strategy for building religious character is needed. This service program aims to internalize Islamic values based on local wisdom among youth. The method used is Participatory Action Research (PAR) with stages ranging from problem identification, planning, implementation, monitoring, and reflection. The program successfully increased youth participation in religious activities, fostered awareness of local traditions aligned with Islamic values, and strengthened synergy between youth, religious leaders, and village governments. In addition, the program also increased Islamic digital literacy among youth through creative content and discussion forums. The results show that the integration of local wisdom and Islamic values in a contextual manner is effective in shaping the religious character of youth. The contribution of this service is to provide an innovative and sustainable youth empowerment model.